Traditional architectural type simulation strategy to fulfil environmental - Abass Ali Hamza; Kais Abdulhusein Abbas (Iraqi Journal of Architecture and Planning, 2018)
In last decades, many architectural tendencies has appeared, that adapting sustainability, with various nominations, but with same or close meanings that refer to same concept. It's all dealing with principles, characteristics, dimensions, and elements of sustainable design, but it were lack to such a comprehensive framework treatment method. which resulting with abstrusely vision for the designer, globally and locally, to determine lineaments of design strategy, that depending on an environmental fundament, with sustainable impression. This abstrusity is the "research problem". This strategy may be strike from fundamental environmental design concept. There for, the research, suppose that, there is an ability to create general conceptual framework, can be used to specify or determine lineaments of design strategies, depending on an environmental idea, that able to give the project such a sustainability characteristic. According to this, the research aim specified as formulating general conceptual framework that having ability to assess projects or architectural designs, and specify or recognize adopted design strategy that strike from sustainable environmental fundament.To fulfill the aim, the research contains three terms. The first one focused on environment and sustainability, in order to understand accredited fundaments, which used to formulate sustainable environmental assessment and design systems, and to produce such a procedural definition for sustainable environmental design. Second term utilize results of former term to formulate a comprehensive theoretical framework, with primary terms and secondary indicators, which inserted in separated table to be implement in term three on selected project (modern courtyard house) to get results which discussed with its two sides, theoretical and practical, to put results and conclusions.